FlyBase: a guided tour of highlighted features. Issue 4 (10th March 2022) - Gramates, L Sian; Agapite, Julie; Attrill, Helen; Calvi, Brian R; Crosby, Madeline A; dos Santos, Gilberto; Goodman, Joshua L; Goutte-Gattat, Damien; Jenkins, Victoria K; Kaufman, Thomas; Larkin, Aoife; Matthews, Beverley B; et al.
Abstract: FlyBase provides a centralized resource for the genetic and genomic data of Drosophila melanogaster . As FlyBase enters our fourth decade of service to the research community, we reflect on our unique aspects and look forward to our continued collaboration with the larger research and model organism communities. In this study, we emphasize the dedicated reports and tools we have constructed to meet the specialized needs of fly researchers but also to facilitate use by other research communities. We also highlight ways that we support the fly community, including an external resources page, help resources, and multiple avenues by which researchers can interact with FlyBase.